Hospital accreditation in Iran: A qualitative case study of Kerman hospitals. (8th January 2018) - Nekoei‐Moghadam, Mahmood; Amiresmaili, Mohammadreza; Iranemansh, Mohammadhosein; Iranmanesh, Mahla
Summary: Background: According to published evidence, accreditation is one of the evaluating tools in health care organizations. But, there is disagreement among authorities and experts in this regard. This study aims to investigate the evaluation of hospital accreditation in an Iranian context. Methods: In this qualitative study, a purposive sample of 170 informants was used. Semi‐structured interviews were conducted to gather data, which were analyzed using a framework analysis method. Results: Elicited themes were categorized into the domains of strengths of accreditation, weaknesses of accreditation, and accreditation model. The results showed that promoting a culture of quality management and patient safety can resolve many of the problems of an accreditation program. This cannot be achieved without a good working knowledge of accreditation and a strategy to diminish nervousness about the programme on the part of staff. Conclusion: The potential impacts of these findings highlight that a comprehensive consideration of the identified inconsistencies is required for a successful implementation of accreditation in Iran. Meetings with professionals and conferences can be considered effective ways of achieving this. Originality/value: It is hoped that our results will facilitate a reformulation of Iran's health policy.